Analisis Beban Kerja dan Kompetensi Sumber Daya Manusia terhadap Efektifitas Kegiatan Stevedoring Petikemas di Pelabuhan - Sahara, Siti; Armanda, Novandu Rio (Advances In Social Humanities Research, 2024)
This study discusses the analysis of workload and human resource competencies on the effectiveness of container loading and unloading activities at the port. The research was conducted at Tanjung Priok Port, North Jakarta, using interview and observation methods. The results show that workload can affect loading and unloading activities at the port, and it is important for companies to consider these factors to maintain safety, worker welfare, productivity, and profitability. High-risk jobs require competence in teamwork, good communication, and specialized skills such as operating heavy equipment. Work motivation is also important to improve morale and efficiency. Companies need to provide training and support to workers to develop competencies and work motivation. Some work motivation factors include work safety, efficiency, labor, and job satisfaction. Many studies have been conducted on competence and performance in various fields, including in ports. Training, supporting activities, and additional time off are some of the ways companies can increase work motivation.